Pemodelan Status Kesehatan Pasien Medical Check Up Klinik Handil Muara Jawa Dengan Regresi Logistik Biner - Rakhmanto Anugrah Darmawan; Darnah Andi Nohe; Desi Yuniarti (EKSPONENSIAL, 2016)
Health is a major human needs are also priorities in human life. many types of health providers available to the community as an example of health care clinics were organized promotive, preventive, curative and rehabilitative. Handil clinics serve patients Muara Jawa Medical Check-Up for the workers of the company or the public. To analyze the factors that affect the health of a patient Medical Check Up can use logistic regression analysis. Logistic regression analysis is an analysis that describes the relationship between the response variable is binary with explanatory variables that can be either qualitative or quantitative variables variables. Based on the research results, we concluded that of the testing parameters, only gender and companies that significantly affect the patient's health status.